DIAXOZIDE INDUCED THROMBOCYTOPENIA IN TREATMENT OF INSULINOMA - Ooi, Xin-yi; Lachumanan, Deviga; Rajoo, Subashini; Bidin, Mohd Badrulnizam Long (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Insulinoma is a rare neuroendocrine tumor. Hypoglycaemia due to insulinoma is be managed by diaxozide, a benzothiadiazine derivate with antihypertensive and hyperglycemic activities prior to definitive surgery. CASE A 65-year-old female was admitted with hunger pangs, sweating and giddiness after a large carbohydrate meal and weight gain of 14 kg in 2 years. On fasting, she developed symptomatic hypoglycaemia within 2 hours with random blood glucose 2.1 mmol/L, serum insulin 1213 pmol/L (N 17.8-173), C-peptide 7784 pmol/L (N 367-1469) and cortisol 598.5 nmol/L. CT pancreases showed a 5 x 5.1 x 5.3 cm irregular walled lesion with coarse calcifications at the tail of pancreas (HU 13-15) with no septation- likely insulinoma. She was started on diaxozide for endogenous hyper- insulinemic hypoglycaemia with dose titrated up to 400 mg/day. One week after diaxozide initiation, she developed symptoms of diazoxide overdose, fever and thrombocytopenia (nadir level 10 x 109/L) with no source of infection. Diaxozide was stopped and she was switched to subcutaneous octreotide 100 mg TDS. Symptoms of overdosage, fever, and thrombocytopenia resolved after 4 days of stopping diaxozide. She then underwent distal pancreatectomy which was curative. Thrombocytopenia is a rare complication of diaxozide and occurs due to platelet destruction from antibody formation. It is dose dependent and occurs 13-23 days after initiation of diaxozide and resolution will occur after discontinuing diaxozide. CONCLUSION Although thrombocytopenia is a rare complication of diaxozide, close monitoring of platelet count is needed to prevent complications.